Are Informal Workers Secondary Workers?: Evidence for Argentina - María Laura Alzúa (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2008)
Empirical studies attempting at testing dualism in developing countries often rely on an ex-ante definition of the primary and the secondary sector. Many times this methodology causes biases in the estimation due to sample selection problems. Also, such definitions may be arbitrary sometimes. We use twenty seven years of Household Data in order to test for the existence dual labor markets in Argentina. We estimated an endogenous switching model with unknown regime without defining ex-ante sector attachment. We find evidence of dualism for both periods analyzed. However, the diferences between the two sectors have signicantly changed over time. Finally, our estimations also corroborate the fact that using the usual ex-ante definition of sector attachment may not be adequate for testing dualism.
Keywords: 330; Arbeitsmarktsegmentation; Argentinien